Institutions and business customer experience: The role of interfunctional coordination and service co-design - Jose L. Ruiz-Alba; María J. Quero; Pablo J. López-Tenorio (European Research on Management and Business Economics (ERMBE), 2023)
This paper contributes to a better understanding of the complex phenomenon of institutions and the moderation of the main antecedents of business customer experience. Following a combination of literature review and three fieldworks, the main antecedents of business customer experience have emerged: interfunctional coordination, customer engagement and participation in the co-design of services. The role of institutions (level of formalisation) has also been considered as a possible moderator. Consequently, a conceptual framework has been developed which includes seven research propositions. The first four research propositions are related to the main elements of the model and suggest new relationships among constructs. The other three research propositions are suggested and empirically examined using Fuzzy-Set Qualitative Comparative Analysis to find causal configurations and to identify pathways that lead to business customer experience. Necessity and sufficiency of conditions that lead to a positive business customer experience are discussed for both scenarios of high and low formalisation of institutions.
Keywords: M31; 650; Institutions; Business customer experience; Interfunctional coordination; Service co-design